Conditioned Medium of Mesenchymal Stem Cells Prevents Degenerative Changes in Ankle Osteoarthritis in Rat Models. Issue 1 (January 2022) - Guss, Daniel; Koohi-Hosseinabadi, Omid; Zarei, Moein; Lubberts, Bart; DiGiovanni, Christopher W.; Tanideh, Nader
Category: Ankle; Ankle Arthritis; Basic Sciences/Biologics; Trauma Introduction/Purpose: Osteoarthritis (OA) is the most common degenerative joint disorder, characterized mainly by progressive articular cartilage degradation, subchondral bone thickening, osteophyte formation, and synovial inflammation. About 80% of ankle OA is believed to be post-traumatic and affects the younger population leading to a higher risk of disabilities during life. Mesenchymal stem cells (MSCs) have shown promising effects in preventing the degenerative process of OA via paracrine effect and great differentiation potential. Recently, using chondrocyte conditioned medium (CCM) that contains all necessary secretomes was shown to enhance MSC differentiation and regeneration of the cartilage tissue. In this study, we aimed to assess the effects of intraarticular injection of MSCs plus CCM on the degenerative process of monoiodoacetate (MIA)-induced ankle OA in rats. Methods: Fifty male rats were randomly divided into 5 groups (n=10): Non-treated control group (C); the group treated with intra-articular Hyaluronic acid (HA). Hyaluronic acid has shown beneficial effects on the degenerative process of OA in different reports. The other treatment groups received intraarticular synovial derived MSCs (5′10 5 ), intraarticular CCM, and intraarticular MSCs combined with CCM (MSC+CCM), respectively. Induction of ankle OA was conducted via 1 mg MIA injection in the right tibiotarsal joint for two consecutive days. Three months after starting the treatments, radiological assessments of joint space width (Normal=0, reduced=1, abcent=2) and osteophytes of the tibia and talus (No osteophyte=0, small=1, moderate=2, severe=3) were performed. Ankle specimens were obtained for histopathological examination of the joint surface, matrix, cell distribution, cell viability, subchondral bone, and mineralization; lower scores indicated more severe damages. Scores for each assessment were recorded. Mann-Whitney U test was used for comparisons and p-value<0.05 was considered statistically significant. Results: Our findings showed significant differences between the controls and the treatment groups regarding all pathological scores including joint surface, matrix, cell distribution, cell viability, subchondral bone, and mineralization, that were higher and radiological scores including joint space width and osteophytes of the tibia and talus that were lower in the controls (P<0.05; Figure 1). Among the treatment groups, HA-treated rats showed significantly lower pathological and higher radiological scores compared to CCM, MSC, and MSC+CCM (P<0.05). Among CCM, MSC, and MSC+CCM treated groups, no significant difference was found regarding the pathological and radiological scores (P>0.05). However, although not statistically noticeable, the MSC+CCM group showed slightly better outcomes, both radiologically and histopathologically, compared to the MSC and CCM groups (Figure 1 ). Conclusion: Our results showed that the combination of CCM can have a similar effect on the degenerative changes in ankle OA. However, the combination of MSC+CCM showed better scores regarding pathological and radiological evaluation. Although further studies with a greater population seem to be needed to validate these outcomes, our study indicates the efficacy of CCM in reducing the degenerative rate of OA. CCM is also known as 'secret factors' since it is still a 'black box' in terms of identifying its content and effects.